IMPROVING ANTIBACTERIAL, THERMAL AND MECHANICAL PROPERTIES OF PVA BIOCOMPOSITES REINFORCED WITH TIMOHO FIBER NANOCELLULOSE - Suteja Suteja; Syarif Hidayatullah; Ahmad Akromul Huda (Protech Biosystems Journal, 2025)
Polyvinyl alcohol (PVA) has promising potential as gas purification membrane and bioplastic substitute for conventional materials. PVA material was reinforced with nanocellulose timoho fibers (NCT). Ten grams of NCT, 30 mL of distilled water, and 10 grams of PVA were stirred (500 rpm) at <80 oC on a magnetic stirrer until gel formed, then spread on a Petri dish and dried in an oven at 50 °C for 21 hours. The elongation, tensile strength, and elastic modulus test results of PVA-NCT biocomposites showed increases of 21%, 29.97%, and 31.57%, respectively, compared to PVA biocomposites. This was due to the role of NCT as reinforcing agent and the mobility of PVA when tensile test. SEM morphology showed a fine speckled surface due to clumping. The thermal resistance of biocomposite increased due to the good interfacial bonding between NCT and the PVA matrix, thereby reducing the rate of weight loss. Exothermic reactions occurred in both biocomposites. The PVA biocomposite had a melting temperature of 110.34 °C, and PVA-NCT biocomposite 119.83 °C. The antibacterial activity of the PVA biocomposite has a lower inhibitory power compared to the PVA-NCT biocomposite. These biocomposites can be used for membrane materials and environmentally friendly bioplastics.